Bienestar Universitario de los estudiantes de la Universidad T´écnica de Cotopaxi extension La Maná. Proyecto para la creación de un departamento de Bienestar Estudiantil en el perÍodo 2010-2011. - Medina López, Enry Gutember (2011)
This investigation is the original result, that was done in Cotopaxi Technical University “La Maná” through a positive proposal about the necessity of a Student Welfare Department. The main idea is to provoke discussion about the concept of universitary welfare and its application in the people who implement the institutional policies to help getting the objectives of democratization and equity that C.T.U “La Maná” has carried out since eight years ago. The intention of this investigation had emphasized in identifying the students´ needs and research if there is a Student Welfare Department that cares in the university community orientation since The Cotopaxi Technical University as a Superior Education Institution which is public, is obligated to account for its actions to the society. As an answer to this situation, arise the possibility of incorporating the Student Welfare Department to the institution, element that would be an important part in the design of the institutional development strategic plan in order to motivate students to keep studying and being part of the professional level. The methodology is based on the qualitative focus with a descriptive diagnostic level, besides the documental investigation was used. About the gathering of information was used the interview and the instruments as the questionnaire. In the processing of information were used the statistics techniques for making the tables and diagrams in Excel program, which served as the basis for conclusions and recommendations.